Saving the Mahachai Betta: Genetic Erosion and Conservation Priorities Under Urbanization Pressure - Nguyen, Ton Huu Duc; Budi, Trifan; Pongsanarm, Tavun; Panthum, Thitipong; Singchat, Worapong; Muangmai, Narongrit; Chaiyes, Aingorn; Suksavate, Warong; Dokkaew, Sahabhop; Griffin, Darren K.; Duengkae, Prateep; Srikulnath, Kornsorn (My University, 2025)
Background/Objectives: Mahachai Betta (Betta mahachaiensis) is a bubble-nesting fighting fish endemic to brackish habitats in Bangkok, Samut Sakhon, and Samut Prakan, where rapid urbanization and industrial growth threaten persistence. We evaluated genetic structure and diversity across 10 populations (81 individuals) to inform conservation planning. Methods: This study combined microsatellite genotyping (13 loci) with ecological niche modeling to assess genetic variability, population connectivity, and landscape–environmental drivers of differentiation. Results: Habitat loss and fragmentation were associated with reduced gene flow and decreased genetic diversity. Mean allelic richness was 2.65 and expected heterozygosity ranged from 0.20 to 0.46, with FST values up to 0.400. Forward simulations predicted severe erosion of diversity within the next 12.5–37.5 years. Populations showed clear genetic subdivision, most pronounced in Samut Prakan and Samut Sakhon, with two Samut Sakhon populations (SKN3 and SKN7) reflecting strong environmental heterogeneity. Conclusions: Improving habitat connectivity and intensifying local community engagement are priority actions to enhance the resilience and long-term persistence of Mahachai Betta. This study provides the first integrated genetic and landscape-based assessment of the species, highlighting its rapid genetic erosion under urbanization and offering a foundation for targeted, evidence-based conservation strategies.
Keywords: conservation; fighting fish; genetic diversity; salinity